Internal and external pressures, facilitators and barriers towards accrual accounting implementation in Malaysian Federal Government - Saiban, Norlailawati (2020)
The Malaysian Federal Government has adopted the modified cash basis of accounting in the preparation of its annual financial statement since the year 2005. Starting from 2011, the government has declared that the Malaysian Federal Government should take over the accrual accounting for better fiscal discipline management and to improve financial and management accounting procedures through complete sight of government assets and financial obligation. Nevertheless, entire implementation of accrual accounting in the government pace few encounters such as the compressed timeframe, concurrent policy and new accounting system development, high training cost as well overseeing the variety itself. To date, Malaysia is making the final preparations for a journey towards adopting a full accrual accounting standard with the directive to present the Financial Statement for the year 2021 in the Parliament. The objective of this study is to find out the relevant factors determine the implementation. The factors are internal pressures, external pressures, facilitators, and barriers. Besides, this study is significant to encompass the application of a contingency model in accounting change that derived from contingency theory as the research theoretical framework. The total of 171 respondents of this study has been taken with the purposive (judgmental) sampling from all accountants who are attached to the Accountant General Department; Head Quarters and Self Accounting Department located in the Federal Government Administrative Centre of Putrajaya and Kuala Lumpur. The result indicates that the internal pressures, external pressures, facilitators, and barriers are positively significant influence towards the accrual accounting implementation in Malaysian Federal Government. The internal pressures have a strong positive correlation, while the barriers have a weak positive correlation with the accrual accounting implementation. Meanwhile, both the external pressures and facilitators have a moderate positive correlation with the accrual accounting implementation in Malaysian Federal Government. These findings are important for the government to come hold the appropriate actions to defeat the future challenges in formulating accounting policy, standards, and systems in the public sector. In ordination to reach a successful implementation of accrual accounting for federal or state government, the Accountant General Department need to play more active roles and may improve their planning programs to overcome barriers and to ensure internal pressures, external pressures and facilitators have been rectified.